Alienation In Leo Tolstoy's Anna Karenina: A Marxist Approach - Puspitasari, Titra (2005)
This study investigates how the major character's alienation is portrayed in Leo Tolstoy's Anna Karenina, specially viewed from Marxist approach. Therefore, the study analyzes the novel in terms of its structural elements and based on Marxist perspective. This study uses the qualitative study. The primary data source is the novel itself. The secondary source is books and other resources that support the analysis. The method of collecting data is library research and the data analysis is descriptive. Based on the analysis, the writer draws some conclusions as follows; First, Anna Karenina, as a literary work, has a close relationship with the social reality of Russian higher-class society in the late nineteenth century. Second, Anna Karenina tells about alienation and criticizes the materialistic orientation at that time. Third, social stratification in the society results alienation.